Effect of Age on Clinical Outcomes in Elderly Patients (>80 Years) Undergoing Percutaneous Coronary Intervention : Insights From a Multi-Centre Australian PCI Registry - Papapostolou, S.; Dinh, D.T.; Noaman, S.; Biswas, S.; Duffy, S.J.; Stub, D.; Shaw, J.A.; Walton, A.; Sharma, A.; Brennan, A.; Clark, D.; Freeman, M.; et al. (ELSEVIER SCIENCE INC, 2021)
Objectives: To evaluate the effect of age in an all-comers population undergoing percutaneous coronary intervention (PCI). Background: Age is an important consideration in determining appropriateness for invasive cardiac assessment and perceived clinical outcomes. Methods: We analysed data from 29,012 consecutive patients undergoing PCI in the Melbourne Interventional Group (MIG) registry between 2005 and 2017. 25,730 patients <80 year old (78% male, mean age 62±10 years; non-elderly cohort) were compared to 3,282 patients ≥80 year old (61% male, mean age 84±3 years; elderly cohort). Results: The elderly cohort had greater prevalence of hypertension, diabetes and previous myocardial infarction (all p<0.001). Elderly patients were more likely to present with acute coronary syndromes, left ventricular ejection fraction <45% and chronic kidney disease (p<0.0001). In-hospital, 30-day and long-term all-cause mortality (over a median of 3.6 and 5.1 years for elderly and non-elderly cohorts, respectively) were higher in the elderly cohort (5.2% vs. 1.9%; 6.4% vs. 2.2%; and 43% vs. 14% respectively, all p<0.0001). In multivariate Cox regression analysis, estimated glomerular filtration rate (eGFR) <30 mL/min/1.73 m2 (HR 3.8, 95% CI: 3.4–4.3), cardiogenic shock (HR 3.0, 95% CI: 2.6–3.4), ejection fraction <30% (HR 2.5, 95% CI: 2.1–2.9); and age ≥80 years (HR 2.8, 95% CI: 2.6–3.1) were independent predictors of long-term all-cause mortality (all p<0.0001). Conclusion: The elderly cohort is a high-risk group of patients with increasing age being associated with poorer long-term mortality. Age, thus, should be an important consideration when individualising treatment in elderly patients.